PENGEMBANGAN MEDIA PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR INFORMATIKA SISWA SMK - Oktapia, Vina; Lisa, Yasinta; Tuah, Yayan Adrianova Eka (JUTECH : Journal Education and Technology, 2024)
This research is research into the development of learning media by utilizing articulate storylines to improve student learning outcomes in computer systems material. So far, the learning carried out still does not use learning media because teachers more often use conventional learning media, causing students to be less able to explore in learning. The research method refers to development research using the ADDIE model. The results of the product feasibility test by media experts and material experts obtained an average score of 76.04% on the "Fine to Use" criteria and 95.83% on the "Very Suitable to Use" criteria. In small-scale trials, an N-Gain value of 74.60 was obtained in the "High" category with a readability response from Guru users of 92.50%. The results of wide-scale trials obtained an N-Gain value of 75.00 in the "Very High" category. Teacher User Readability Response is 97.00%. It can be concluded that the media product developed is "Very Good" in its use. This shows that learning media utilizing an articulate storyline is suitable for use and is able to improve student learning outcomes in class X informatics subjects at SMK Negeri 1 Nanga Pinoh